(3GdJhWFIs - (3YeQ Hf eMeO Hf YeQ Hf YHO Gddg GdCROj, CHh Ydj, GdTdhHjfj Ch GdTdhHjf,J (B645 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj JaVd YdjfG hJee gPg GdLedI GdJj QSeJ gfG JhWFI bhGfjf GdebOeI s
(3BNQgG (B:s
(3heKd Pdc EdG Cf GdRjGOI ajg ddKGfj Ydi GdChd fMh dbO HGJ, hbO SeY, hdbO Rjf, heG CTHg Pdc s
(3fSNI HBNQgG JedcGJ CbOegG (B778(3g``s
(3HChdgG agQS ddehVhYGJ UfY eJCNQkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B62 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B316s
Keywords: (3GdfMhs